INOVASI DIGITAL DALAM PEMBERDAYAAN UMKM: IMPLEMENTASI AUGMENTED REALITY PADA PRODUK KUE BASAH KHAS PALEMBANG - Putri, Aulia Utami; Imania, Katriza; Rahmawati, Annisa; Saputri, Efrilia Wanda; Fathiyah, Nabila Trisya (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Palembang is known for its variety of traditional culinary products, including kue basah (traditional wet cakes), which serve both as a cultural identity and an economic opportunity for micro, small, and medium enterprises (MSMEs). One of the main challenges faced by these MSMEs is low brand recall and brand recognition, particularly among younger consumers who rely on digital media as a reference for purchases. This community service activity aimed to empower kue basah MSMEs through digital innovation by implementing an interactive catalog based on Augmented Reality (AR) as a marketing strategy. The activity employed a participatory approach, including partner situation analysis, AR catalog design, product photography and AR training, and evaluation through pre-tests and post-tests. The training involved the owner and employees of MSMEs Bunda Rayya as well as members of the South Sumatra Cake and Culinary Entrepreneurs Association (Aspenku). The AR catalog enabled consumers to explore 3D product visuals, descriptions, and additional information interactively. Evaluation results showed an increase in the participants’ average score from 62 to 79, with paired t-test analysis indicating a highly significant difference (t(9) = 3.28; p < 0.01), demonstrating the effectiveness of the training in improving product photography skills and AR utilization. This activity enhanced MSMEs’ capacity for digital promotion, strengthened the cultural identity of Palembang’s culinary heritage, fostered consumer engagement, and expanded market opportunities. These findings provide a foundation for the development of sustainable empowerment programs and the replication of digital innovation in other traditional culinary MSMEs.